Papel de los genes srrA y msnA en la biosíntesis de lovastatina por Aspergillus terreus - Bibián León, María Esmeralda (Universidad Autónoma Metropolitana, 2015)
Lovastatin is a drug of great industrial importance for reducing blood cholesterol levels, also in recent years is found as potential cancer therapeutic functions. Its conventional production takes place in SmF, however, in recent years has aroused great interest in the production SSF by high production, among other advantages over liquid medium. This solid medium physiology there are certain environmental stimuli that are noted to fungus found on solid medium. These stimuli must be detected and then transduced, firing a number of events at the molecular level. ROS accumulation is also different in SSF and SmF, this oxidative stress preceding the biosynthesis of secondary metabolites, such as lovastatin, is necessary and recently demonstrated that ROS are regulating the biosynthesis of lovastatin at the transcriptional level. Furthermore there is evidence that transcription factors in response to oxidative stress (as SrrA and MsnA) could be regulating the biosynthesis of lovastatin in response to the ROS. So this work focused on the study of the SrrA and MsnA genes as potential regulators of the biosynthesis of lovastatin. The function of genes silencing was assessed using a strategy that is based on the attenuation of genes via RNAi machinery itself which triggers a cell, and thus evaluate changes possible functions of the gene. Silencing constructs the SrrA and MsnA genes, were performed separately. Transformants were obtained with attenuated gene srrA (SisrrA) and msnA (SimsnA). Regarding the effects radial growth, sporulation, oxidative stress, wall stress (only for SisrrA) and lovastatin production were evaluated. SimsnA phenotype showed slight resistance to oxidative stress (4/7 transformants), as for the linear growth rate showed only slight deficiency. There was a decrease in the rate of sporulation of about 70% (3/7) and lovastatin terms of production, not a strong effect was found. The SisrrA showed no effect on oxidative or wall stress, only had a lower rate of sporulation, but as for radial growth on PDA medium there was a decrease in the growth rate, and in the midst Power increased, but the phenotype more interesting was that one of the transformants produced more pigments (secondary metabolites) means the Power, which took a dark red color. And as expected, in production of lovastatin was presented a sharp increase in SSF (up 180 %) but an abrupt decrease in SmF (up to 90%). In this work it has successfully demonstrated that the gene msnA exists in Aspergillus terreus, however, its function is still unknown. It has also been shown that SrrA does participate in regulating the biosynthesis of lovastatin, and most importantly, physiology part of the solid medium, however, still unknown mechanism.; La lovastatina es un fármaco de gran importancia industrial por reducir los niveles de colesterol en sangre, además en los últimos años se le han encontrado funciones terapéuticas potenciales como el cáncer. Su producción convencional se lleva a cabo en FL, sin embargo, en los últimos años se ha despertado un gran interés en la producción en FS por su elevada producción, entre otras ventajas, con respecto a medio líquido. En esta fisiología del medio sólido existen ciertos estímulos ambientales que anuncian al hongo que se encuentra en medio sólido. Estos estímulos deben ser detectados y entonces transducidos, disparando un número de eventos a nivel molecular. La acumulación de EROs también es diferente en FS y FL, este estado oxidante que precede a la biosíntesis de metabolitos secundarios, como la lovastatina, es necesario y recientemente se demostró que las EROs están regulando la biosíntesis de lovastatina a nivel transcripcional. Además hay evidencia de que factores de transcripción en respuesta a estrés oxidante, como SrrA y MsnA, pudieran estar regulando la biosíntesis de lovastatina en respuesta a las EROs. Por lo que este trabajo se enfocó en el estudio de los genes srrA y msnA como posibles reguladores de la biosíntesis de lovastatina. La función de los genes se evaluó mediante silenciamiento, estrategia que se basa en la atenuación de los genes a través del RNA de interferencia que desencadena una maquinaria propia de la célula, y de esta forma, se evaluan los cambios como posibles funciones del gen. Se realizaron construcciones de silenciamiento con los genes srrA y msnA, por separado. Se obtuvieron transformantes con el gen atenuado srrA (SisrrA) y msnA (SimsnA). Se evaluaron los efectos en cuanto a crecimiento radial, esporulación, estrés oxidante, estrés de pared (sólo para las SisrrA) y producción de lovastatina. El fenotipo de las SimsnA presentaron ligera resistencia al estrés oxidante (4/7 transformantes), en cuanto a la velocidad lineal de crecimiento sólo una presentó ligera deficiencia. Hubo una disminución en el índice de esporulación de alrededor del 70% (3/7) y en cuanto a producción de lovastatina, no se encontró un efecto contundente. Las SisrrA no presentaron efecto en sensibilidad a estrés oxidante ni resistencia a estrés de pared. Una de las transformantes (T2) tuvo un índice de esporulación menor. En cuanto a crecimiento radial, en medio PDA hubo una disminución en la velocidad de crecimiento, y en medio Power un aumento; además el fenotipo de una de las transformantes (T2) produjo más pigmentos (metabolitos secundarios) en medio Power, el cual tomó una coloración roja. Y como era de esperarse, en cuanto a producción de lovastatina se presentó un fuerte aumento en FS (de hasta 180%) pero una disminución abrupta en FL (de hasta el 90%). En este trabajo se ha logrado demostrar que el gen msnA existe en Aspergillus terreus además de que SrrA sí participa en la regulación de la biosíntesis de lovastatina, y lo más importante, forma parte de la fisiología del medio sólido, sin embargo, su mecanismo y función precisa aun se desconocen.